2009
DOI: 10.1016/j.bbrc.2009.08.163
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson’s disease kinase LRRK2 autophosphorylates its GTPase domain at multiple sites

Abstract: Mutations in Leucine-rich repeat kinase 2 (LRRK2) are a common cause of inherited Parkinson's disease (PD). The protein is large and complex, but pathogenic mutations cluster in a region containing GTPase and kinase domains. LRRK2 can autophosphorylate in vitro within a dimer pair, although the significance of this reaction is unclear. Here, we mapped the sites of autophosphorylation within LRRK2 and found several potential phosphorylation sites within the GTPase domain. Using mass spectrometry, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 29 publications
6
139
0
Order By: Relevance
“…During the revision stage of this paper, Greggio et al reported on the identification of autophosphorylation sites within the ROC domain of LRRK2 (25), some of which (e.g., Thr1410, Thr1491) correspond to those determined in this present study.…”
Section: Acknowledgmentmentioning
confidence: 80%
“…During the revision stage of this paper, Greggio et al reported on the identification of autophosphorylation sites within the ROC domain of LRRK2 (25), some of which (e.g., Thr1410, Thr1491) correspond to those determined in this present study.…”
Section: Acknowledgmentmentioning
confidence: 80%
“…LRRK2 has been found to autophosphorylate > 20 serine and threonine residues in vitro 37, 50, 56, 57, 58, 59, 60, 61. The majority of the autophosphorylation sites reside in the ROC domain, with only a few in the COR and kinase domains (Fig.…”
Section: Importance Of Lrrk2 Autophosphorylation and Constitutive Phomentioning
confidence: 99%
“…Reciprocal regulation of GTP binding by the kinase domain may also occur, as LRRK2 autophosphorylates several residues within the ROC domain. Phosphorylation of T1491 and T1503 residues apparently diminishes GTP binding [24][25][26][27][28][29], suggesting that LRRK2 GTPase may be functionally downstream of the kinase activity [30], although more complex situations may occur. These suggestions show that there is intramolecular communication between different LRRK2 domains, pointing out how complex the molecule is.…”
Section: Introductionmentioning
confidence: 99%